The predictive and incremental validity of the German adaptation of the Static-2002 in a sexual offender sample released from the prison system - Martens, Ronja (Legal and criminological psychology, 2017)
Purpose. The aim of this study was to examine the predictive validity of the German adaptation of the Static-2002 and to compare it with the results of the Static-99. Method. The predictive validity of Static-2002 was investigated in a sample of n = 452 sexual offenders released from the Austrian Prison System. The instrument was coded retrospectively using file information. Afterwards, the predictive estimates of the Static-2002 were related to officially documented reconviction data. Results. The Static-2002 was found to have large effect sizes for predicting sexual, violent, and general recidivism (area under the receiver operating characteristic curve [AUC] = .78, .75, .75, respectively) for the total offender sample. For the general sexual offender sample, it did not predict reoffence significantly better than the Static-99 ([AUC] = .77, .72, and .72, respectively). However, the Static-2002 was found to perform better in the child molesters subsample (AUC = .83, .74, .75, respectively) than in rapists (AUC = .66, .72, .73, respectively), even though these differences did not reach statistical significance. The Static-2002 was found to have incremental predictive validity beyond the Static-99, but only for general and not for sexual or violent recidivism. Conclusions. Although a replacement of the Static-99 by the Static-2002 cannot be recommended, it has to be emphasized that the Static-2002 yielded large effect sizes in predicting general, violent, and sexual recidivism and, therefore, nevertheless represents an excellent measure for capturing the reoffence risk of sexual offenders.